Analysis of Students’ Errors in Solving Algebraic Function Limit Problems based on Bloom’s Taxonomy - Sakdiah, Sakdiah; Siregar, Rama Nida (IKIP Siliwangi, 2025)
Understanding mathematical concepts is a fundamental component in effective mathematics learning. When students lack conceptual understanding, their ability to solve problems accurately such as in the topic of algebraic function limits is significantly hindered. This study aims to identify the causes of students’ incorrect answers in solving limit problems of algebraic functions based on Bloom's Taxonomy. A qualitative descriptive research method was employed to explore this issue. Data were collected using a written test consisting of three essay questions constructed to represent different levels of Bloom’s Taxonomy, followed by brief interviews with selected students. The research involved Grade 11 students who had previously studied the limit of algebraic functions. The students' answers were analyzed to classify types of errors and identify patterns related to specific cognitive levels. The results indicated that all students answered correctly at the C1 and C2 levels (remembering and understanding). However, at the C3 and C4 levels (applying and analyzing), students commonly made Encoding Errors and Transformation Errors. At the higher cognitive levels C5 and C6 (evaluating and creating) Process Skills Errors and Comprehension Errors were more prevalent. These findings suggest that students struggle more as the cognitive demands of questions increase, indicating a lack of problem solving practice and insufficient exposure to high level thinking tasks. In conclusion, strengthening instructional strategies that target higher order thinking skills is necessary to help students develop deeper mathematical understanding.